Numerical Study of Solid Core Photonic Crystal Fibres with Endlessly Single Mode - Muhammed, Nadia Fateh; Ibrahim, Aseel; Kahdum, Shehab Ahmad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this work, a solid core photonic crystal fibre (SC-PCF) has been designed with endlessly single mode of which both centerd core and holes in the cladding are organized by circles. The designed SC-PCF has a single solid centerd core which is ringed by a six rings hexagonal cladding. The computation of SC-PCF is achieved by using the finite element method (FEM) with perfectly matched layer (PML) boundary condition. All the designed factors like dimensions and distance of both core and cladding areas have varied with an optimized structure. After ending the numerical calculation, the results shows that there are a link between the air hols in the cladding , and the different normalized air hole size.